The Abolishment of Fiduciary on the Object of Fiduciary in Denpasar City - I Kadek Setiawan (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2018)
This study examines the abolishment of fiduciary listed in Articles 16 and 17 of Government Regulation Number 21 of 2015 stating that objects registered with the Ministry of Law and Human Rights through online must be deleted. This is done to ensure a legal certainty for both the debtor and the creditor. The type of research used is empirical juridical research, and data used are primary data, secondary data and tertiary data. The results of data analysis show that the abolishment of fiduciary is carried out by only a part of debtors and creditors. As a result of not abolishing the fiduciary, the debtor cannot guarantee the goods or collateral objects as a fiduciary.